A true Malaysian - Abd Razak, Dzulkifli (2004)
EACH time we celebrate Malaysia Day on Sept 16, the question of Bangsa Malaysia pops up. Where are we in our search for a national identity and culture? As we mull over this question, one cannot help but recall the analogy of a dog's barking to that of a call to prayer made some time ago and wonder what would be the implication of such thinking on the country's future. The fact that it was published in the Bar Council's Infoline (May/June) adds to the concern. Comparing the barking of a dog to human activity is not acceptable under any circumstance, what more associating to activities that are sacred.